The effect of adherence to spectacle wear on early developing literacy: a longitudinal study based in a large multiethnic city, Bradford, UK. Issue 6 (12th June 2018) - Bruce, Alison; Kelly, Brian; Chambers, Bette; Barrett, Brendan T; Bloj, Marina; Bradbury, John; Sheldon, Trevor A
Abstract : Objectives: To determine the impact of adherence to spectacle wear on visual acuity (VA) and developing literacy following vision screening at age 4–5 years. Design: Longitudinal study nested within the Born in Bradford birth cohort. Setting and participants: Observation of 944 children: 432 had failed vision screening and were referred (treatment group) and 512 randomly selected (comparison group) who had passed (<0.20 logarithm of the minimum angle of resolution (logMAR) in both eyes). Spectacle wear was observed in school for 2 years following screening and classified as adherent (wearing spectacles at each assessment) or non-adherent. Main outcome measures: Annual measures of VA using a crowded logMAR test. Literacy was measured by Woodcock Reading Mastery Tests-Revised subtest: letter identification. Results: The VA of all children improved with increasing age, −0.009 log units per month (95% CI −0.011 to −0.007) (worse eye). The VA of the adherent group improved significantly more than the comparison group, by an additional −0.008 log units per month (95% CI −0.009 to −0.007) (worse eye) and −0.004 log units per month (95% CI −0.005 to −0.003) in the better eye. Literacy was associated with the VA, letter identification (ID) reduced by −0.9 (95% CI −1.15 to −0.64) for every one line (0.10 logMAR) fall in VA (better eye). This association remained after adjustment for socioeconomic and demographic factors (−0.33, 95% CI −0.54 to −0.12). The adherent group consistently demonstrated higher letter-ID scores compared with the non-adherent group, with the greatest effect size (0.11) in year 3. Conclusions: Early literacy is associated with the level of VA; children who adhere to spectacle wear improve their VA and also have the potential to improve literacy. Our results suggest failure to adhere to spectacle wear has implications for the child's vision and education.